Tom Roberts-War Alarm..Ban The Bomb! - :::Creator::::::::::::; :::Contributor::::::::::::; :::Editor::::::::::::; University of California, Berkeley:::University place::::::::::::
Silk screen print of a photograph of poet, Tom Roberts. The following text is printed on the poster: "War Alarm.. Ban The Bomb! In Every City... On Every Farm. Stop The War In Viet Nam... Freedom Now To Alabam'...It's Zero Hour Sister, It's Zero Hour Brother...We've Got To Hurry, To Save One Another." TOM ROBERTS appears in the bottom lower right of the poster.